2016
DOI: 10.1007/s10900-016-0165-y
|View full text |Cite
|
Sign up to set email alerts
|

Timeliness of Colonoscopy After Abnormal Fecal Test Results in a Safety Net Practice

Abstract: Background Fecal testing can only reduce colorectal cancer mortality if patients with an abnormal test result receive a follow-up colonoscopy. As part of the Strategies and Opportunities to STOP Colon Cancer in Priority Populations (STOP CRC) project, we examined factors associated with adherence to follow-up colonoscopy among patients with abnormal fecal test results. Methods As part of STOP CRC outreach, Virginia Garcia Memorial Health Center staff distributed 1,753 fecal immunochemical tests (FIT), of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
35
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 26 publications
5
35
0
Order By: Relevance
“…Our observation of the contribution of potentially inappropriate screening because of a recent prior colonoscopy to the follow‐up rate is consistent with findings from prior studies, including 1 that identified recent colonoscopy as a prevalent reason for failure to complete follow‐up and 2 that reported a strong association between colonoscopy history and follow‐up of a positive FOBT/FIT result . Potentially inappropriate screening because of limited life expectancy was relatively rare in our sample (<1%), as also documented in prior studies conducted in samples ages 50 to 75 years .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our observation of the contribution of potentially inappropriate screening because of a recent prior colonoscopy to the follow‐up rate is consistent with findings from prior studies, including 1 that identified recent colonoscopy as a prevalent reason for failure to complete follow‐up and 2 that reported a strong association between colonoscopy history and follow‐up of a positive FOBT/FIT result . Potentially inappropriate screening because of limited life expectancy was relatively rare in our sample (<1%), as also documented in prior studies conducted in samples ages 50 to 75 years .…”
Section: Discussionsupporting
confidence: 91%
“…Our finding that age and comorbidities were negatively associated with follow‐up is consistent with previous reports . Studies that demonstrated no significant association between follow‐up and these factors either restricted the sample to the oldest age groups or excluded those aged >75 years . It is not clear why the effects of age and comorbidity on follow‐up were not fully explained by other patient characteristics, patient behaviors (refusal, private sector colonoscopy use), physician behaviors (inappropriate screening), or environmental factors.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The authors reported that 89% of patients with an abnormal FIT result were referred for follow‐up colonoscopy within 6 months, but only 44% actually underwent diagnostic colonoscopy. This level of follow‐up is consistent with the poor CDE rates reported in cited Veterans Administration, safety net, and other FQHC‐based studies …”
supporting
confidence: 86%
“….A delay in follow-up significantly undermines the benefits of CRC screening, including incidence, mortality, life-years saved, and net costs of screening [4][5][6][7]. Recommendations regarding the time between a positive result and colonoscopy vary between countries, ranging between 30 and 180 days [8][9][10][11][12][13]. In Israel, the Ministry of Health guidelines define the waiting period as 90 days [3,14].…”
Section: Repeated Automated Mobile Text Reminders For Follow-up Of Pomentioning
confidence: 99%